1979
DOI: 10.1111/j.1467-9450.1979.tb00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate reactions to TV‐violence by Finnish pre‐school children of different personality types

Abstract: Children were filmed while watching violent films and their facial expressions were rated from the videotape. After having seen the violent films and after a control film they were filmed while playing in groups of three. The children represented four personality types, aggressive, constructive, submissive, and anxious. While viewing, the aggressive children looked less concentrated than the others, the constructive children showing most tenseness and fear. In the play behaviour, personality accounted for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Researchers have operationalized aggressive behavior in a number of ways, including measuring the intensity of electric shocks administered to another individual (e.g., Bailey & Taylor, 1991;Bushman, 1995;Buss, 1963Buss, , 1966Giancola & Zeichner, 1995a, 1995bTaylor, 1967), pushing and hitting (e.g., Josephson, 1988), monetary or point penalties (e.g., Bjork, Dougherty, Moeller, & Swann, 2000;Check & Dyck, 1986;Netter et al, 1998;Strube, Turner, Cerro, Stevens, & Hinchey, 1984), verbal attack (e.g., Langerspetz & Engblom, 1979), and negative evaluations (e.g., Leibowitz, 1968;Rothaus & Worchel, 1960;Shemberg, Leventhal, & Allman, 1968;Wingrove & Bond, 1998).…”
Section: Definitions Of Personality Aggressive Behavior and Provocamentioning
confidence: 99%
“…Researchers have operationalized aggressive behavior in a number of ways, including measuring the intensity of electric shocks administered to another individual (e.g., Bailey & Taylor, 1991;Bushman, 1995;Buss, 1963Buss, , 1966Giancola & Zeichner, 1995a, 1995bTaylor, 1967), pushing and hitting (e.g., Josephson, 1988), monetary or point penalties (e.g., Bjork, Dougherty, Moeller, & Swann, 2000;Check & Dyck, 1986;Netter et al, 1998;Strube, Turner, Cerro, Stevens, & Hinchey, 1984), verbal attack (e.g., Langerspetz & Engblom, 1979), and negative evaluations (e.g., Leibowitz, 1968;Rothaus & Worchel, 1960;Shemberg, Leventhal, & Allman, 1968;Wingrove & Bond, 1998).…”
Section: Definitions Of Personality Aggressive Behavior and Provocamentioning
confidence: 99%
“…These studies show that pre-school children react most strongly to physical violence on the screen, but that the children also tend to withdraw from scenes of verbal violence between adults (Lagerspetz, Wahlroos & Wendelin, 1978). Personality type (aggressive, constructive, submissive and anxious) predicts more of the children's behaviour in a playsituation after TV watching than their facial expressions when watching, or the type of film shown (Lagerspetz & Engblom, 1977).…”
Section: Aggression and Child Developmentmentioning
confidence: 81%
“…This specific item was to begin with considered to be the best anxiety measure (cf. Lagerspetz and Engblom 1979).…”
Section: Differences Between the Age Groupsmentioning
confidence: 99%
“…These two subgroups can be expected to react differently to violent films. Earlier studies (Feshbach and Singer 1971;Lagerspetz and Engblom 1979) have shown that the behaviour of aggressive and nonaggressive children is affected differently by violent films. Aggressive children are known to prefer violent films (Heller and Polsky 1976;Eron 1963) and to more often entertain aggressive fantasies (Huesmann et al 1984).…”
mentioning
confidence: 97%